Hubungan Peer Influence terhadap Munculnya Perilaku Non-Suicidal Self-Injury pada Remaja - Mailaffayza, Qorinatu; Arbi, Dian Kartika Amelia (Universitas Airlangga, 2023)
This research aims to determine whether there is a relationship between peer influence and the emergence of non-suicidal self-injury behavior in adolescents. Peer influence refers to the effect that peers have on an individual's behavior, attitudes, and. NSSI includes five criteria: the behavior involves deliberate self-injury (e.g., cutting, burning, scratching, hitting oneself), the behavior is not done with a conscious intent to commit suicide. This research uses quantitative survey methods. Data analysis of this research used correlation techniques. Results indicated a significant positive relationship (r=0.276; p=0.005<0.05), if there is an increase in peer influence resistance, NSSI behavior also increases.